Influence of foodservice quality on customer satisfaction in the universities of Klang Valley, Malaysia : locals vs internationals. - Salehuddin, Nadzirah; Othman, Mohhidin; Abdul Karim, Mohd. Shahrim; Ghazali, Hazrina
University foodservices in Malaysia have long been catering to the day-to-day meals for their students and staffs, from different cultural backgrounds. As an educational tourism center, these higher education institutions promote to attract more number of international students to further their studies in Malaysia. Since internationals and Malaysians have different perceptions towards food service quality, there are certain challenges for foodservice operators in comparing and fulfilling the needs of both two unique groups. Therefore, the aim of this study is to fill the gap in this area of knowledge. The sample frame for the study was students and staff of universities and colleges from around the Klang Valley area from September to December 2012. Frequency, paired sample t-test, multiple regression analysis and independent sample t-test were used to analyze the data. This study revealed that there are is no significant relationship between customer satisfaction and the respondents’ country of origin, where there is no difference between locals and internationals in terms of Customer Satisfaction. The data had also indicated that ‘Product Quality’ and ‘Value to Customer’ have have significant effect on Customer Satisfaction of both locals, and internationals, and ‘Technological Application’ was an additional factors for local respondents. This paper will significantly contribute in providing a deeper insight into the differing satisfaction levels and foodservice needs of both of these two unique groups of clienteles, thus help guide university foodservice operators in providing satisfactory service to not only one portion of the population, but to all their customers, local and international alike.